2022
DOI: 10.1136/thoraxjnl-2021-218088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of switching from a metered dose inhaler to a dry powder inhaler on climate emissions and asthma control: post-hoc analysis

Abstract: ObjectiveTo compare the effects of switching from a pressurised metered dose inhaler (pMDI)-based to a dry powder inhaler (DPI)-based maintenance therapy versus continued usual care on greenhouse gas emissions (carbon dioxide equivalents, CO2e) and asthma control.MethodsThis post-hoc analysis was based on a subset of 2236 (53%) patients from the Salford Lung Study in Asthma who at baseline were using a pMDI-based controller therapy. During the study patients were randomised to fluticasone furoate/vilanterol (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 16 publications
1
29
0
3
Order By: Relevance
“…For example, in most cases, asthma patients can be safely moved from metered-dose inhalers to dry-powder inhalers, very significantly reducing the total amount of carbon dioxide and other greenhouse gases emitted in asthma management. In Scandinavian countries, 90% of inhalers are now dry-powder, and health outcomes remained the same (Wintemute & Miller, 2020; Woodcock et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in most cases, asthma patients can be safely moved from metered-dose inhalers to dry-powder inhalers, very significantly reducing the total amount of carbon dioxide and other greenhouse gases emitted in asthma management. In Scandinavian countries, 90% of inhalers are now dry-powder, and health outcomes remained the same (Wintemute & Miller, 2020; Woodcock et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this study could not assess this aspect due to the limitations of the NDB Open Data, which does not include patient‐specific information. A post‐hoc analysis of a randomized controlled trial on adults showed that switching from ICS/LABA pMDIs to DPIs improved asthma control in those who switched compared to those who remained on pMDIs 26 . Considering the substantial GHG emissions from ICS/LABA pMDIs in Japan, it may be both safe and effective to replace ICS/LABA.…”
Section: Discussionmentioning
confidence: 99%
“…Encourage practitioner behaviour change to favour DPIs (and SMIs) over pMDIs 1927. A post hoc analysis of 2236 patients in England showed reduced asthma symptoms and greater productivity in daily activities in patients switching from pMDI to DPI 27…”
Section: What Are the Solutions?mentioning
confidence: 99%